2007
DOI: 10.1071/rdv19n1ab16
|View full text |Cite
|
Sign up to set email alerts
|

16 Progesterone Release Patterns From Cue-Mate in Comparison to Other Intravaginal Progesterone-Releasing Devices in Lactating Dairy Cows

Abstract: Various intravaginal progesterone-releasing devices are commercially available and each is impregnated with different amounts of progesterone. An experiment was designed to characterize plasma progesterone release profiles from Cue-Mate in comparison with other commercially available progesterone-releasing devices. Cycling, lactating Holstein cows (n = 60; BCS between 2.0 and 3.0 out of 5) from commercial dairy farms in Argentina were used in 2 replicates. All cows received 2 injections of D+ cloprostenol (PGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
3
1
0
1
Order By: Relevance
“…There were no significant differences between treatment groups in the mean progesterone concentrations of the monitor heifers on each sampling day, confirming results by Rogan et al. (2007) that compared circulating progesterone concentrations of four different implants (implants concentration ranged from 1.0 to 1.9 g P 4 ).…”
Section: Discussionsupporting
confidence: 82%
“…There were no significant differences between treatment groups in the mean progesterone concentrations of the monitor heifers on each sampling day, confirming results by Rogan et al. (2007) that compared circulating progesterone concentrations of four different implants (implants concentration ranged from 1.0 to 1.9 g P 4 ).…”
Section: Discussionsupporting
confidence: 82%
“…Our results were consistent with previously published work in New Zealand anoestrous dairy cows: there was no significant difference in conception rates when comparing the use of a 1.0 g progesterone DIB‐V with a 1.38 g progesterone CIDR® in a FTAI program . Similarly in another study, no differences in peak or mean progesterone concentrations were found in lactating Holstein cows when treated with the 1.9‐g CIDR®, 1.56‐g Cuemate®, 1.38‐g CIDR or 1.0‐g DIB‐V® devices . The use of intravaginal progesterone devices in GnRH‐based programs to improve conception rates has been shown to be most effective in non‐cycling cows .…”
Section: Discussionsupporting
confidence: 92%
“…This result also showed the effect of DIB treatment on plasma P4 concentration was similar to CIDR treatment in Japanese Black cows. This study coincided with the previous report that 7-days treatment with DIB or CIDR for estrus synchronization resulted in similar mean plasma P4 concentration in dairy cows [32], although different P4 doses of CIDR affected plasma P4 concentration in CIDR-synch protocol [19]. In this study, though P4 values on Day 19 were significantly higher in pregnant cows than in non-pregnant cows in DIB and control group, it did not differ in CIDR group.…”
Section: Discussionsupporting
confidence: 91%